2017
DOI: 10.1259/bjrcr.20160055
|View full text |Cite
|
Sign up to set email alerts
|

Solitary pulmonary hyalinising granuloma: a rare cause of pulmonary nodule

Abstract: A pulmonary nodule is a common incidental finding on chest imaging, which includes a wide variety of differential diagnosis. Pulmonary hyalinising granuloma is a rare disease aetiology of pulmonary nodule(s). We report a 74-year-old female who was referred to the respiratory clinic with incidental finding of a solitary pulmonary nodule on chest X-ray. CT confirmed the presence of a 1.2 cm solitary pulmonary nodule in the left upper lobe with no lymphadenopathy. The patient underwent wedge resection, and histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Despite its benign nature, it can often present similarly to metastatic disease3 5 and thus patients can undergo extensive investigation to seek a definitive diagnosis. There is often diagnostic uncertainty around PHG, and the existing literature have indicated that a definitive diagnosis is usually gained only after surgical intervention as in our patient 4 7 8. Recognising the difficulty in making a diagnosis also impacts on a patient’s emotional well-being with, potential for complications from invasive investigations and uncertainty over a potential lung cancer diagnosis, is also important.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Despite its benign nature, it can often present similarly to metastatic disease3 5 and thus patients can undergo extensive investigation to seek a definitive diagnosis. There is often diagnostic uncertainty around PHG, and the existing literature have indicated that a definitive diagnosis is usually gained only after surgical intervention as in our patient 4 7 8. Recognising the difficulty in making a diagnosis also impacts on a patient’s emotional well-being with, potential for complications from invasive investigations and uncertainty over a potential lung cancer diagnosis, is also important.…”
Section: Discussionmentioning
confidence: 93%
“…PHG, though rare, is a recognised cause of benign lung nodules. The disease was first described by Engleman et al in 1977,6 it can present at any age,1 typically with non-specific symptoms and has an excellent prognosis2 3 with no malignant potential 4. The aetiology of PHG is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation